Pengaruh Biaya Promosi Terhadap Jumlah Pengunjung : Studi Kasus Pada Obyek Wisata Kebun Raya Bogor - Supariyani, Hj. Emmy (Jurnal Ilmiah Ranggagading (JIR), 2004)
This research was done to know how far promotionâs influence carried out by Kebun Raya in order to raise number of visitors, how to detect problem it has faced, and how o do anticipation. The result is Y=5,48+1,07X; correlation analysis is r =0.942, degree of correlation between promotion and number of visitor is KD = 88,7364 %. Various matters could be anticipated by many kinds of methods in accordance with the policy established by Kebun Raya. From analysis and result concluded that promotion is able to increase number of visitors. Enumeration result by regression and correlation shows that mix activities has significant influence in raising number of visitors. Keywords : Promotion; Promotion Cost.